Integrating Life Cycle Assessment and System Dynamics in Industrial Land Preparation: A Literature Review Approach - Marantica, Lutfi; Adi, Henny Pratiwi; Mudiyono, Rachmat (ASTONJADRO, 2026)
Industrial estate development in Indonesia plays a crucial role in driving economic growth, yet faces significant sustainability challenges, particularly during the land preparation phase, which involves clearing, leveling, backfilling, and basic infrastructure development. These activities often lead to carbon emissions, land degradation, and ecosystem disruption. Life Cycle Assessment (LCA) methods are widely used to quantitatively measure environmental impacts, such as energy consumption and greenhouse gas emissions, but are static and less able to capture socio-economic dynamics. In contrast, System Dynamics (SD) excels at dynamically modeling variable interactions and evaluating long-term policy scenarios, although it requires valid data. This article reviews previous research and emphasizes the relevance of LCA–SD integration as a comprehensive assessment framework. This integration can quantify environmental impacts while simulating policy scenarios, making it relevant to supporting more sustainable industrial estate development in Indonesia.